Flow-directed vs. goal-directed strategy for management of hemodynamics. Issue 3 (June 2016) - Magder, Sheldon
Abstract : Purpose of review: For the past 15 years, there has been a strong push to use goal-directed protocols for resuscitating critically ill patients and to manage perioperative patients. However, recent large clinical trials have failed to find evidence of improved outcome with this approach. Recent findings: A striking feature in the recent three large prospective randomized trials of septic patients and the one in high-risk perioperative patients is that outcomes in the control groups have markedly improved. This implies improvement in care and clinical acumen. Perhaps the clinical approach should be more toward further helping clinicians with their clinical choices. A good example is cardiac output. The objective of most hemodynamic interventions is to increase cardiac output. It would thus make sense to assess what happened to cardiac output after the intervention to determine if the intervention actually increased cardiac output. If it did not, another therapy should be chosen. I call this a flow-directed responsive protocol. Summary: A clinical approach that uses monitored values such as cardiac output as a feedback tool to evaluate the response to therapeutic interventions in individual patients may be better than protocols that set fixed targets for all study participants.